Effects of parthenolide on amino acid metabolism and oxidative stress in lung adenocarcinoma based on quantitative proteomic analysis, targeted amino acid metabolomics, network pharmacology, and experimental validation - Liu, Jiye; Liu, Yu; Li, Jiachun; Shen, Shuang (Frontiers in Oncology, 2025)
BackgroundLung adenocarcinoma (LUAD) causes millions of deaths annually worldwide. Parthenolide (PTL), extracted from traditional Chinese herbal medicines, has various biological activities. In this study, we investigated the effects of PTL on amino acid metabolism and oxidative stress in LUAD cells.MethodsThis study identified differential proteins and potential mechanisms of action of PTL in LUAD cells through label-free quantitative proteomics and protein-protein interaction networks. Combined with targeted amino acid metabolomics, we confirmed the results of GO and KEGG analyses. On this basis, the potential targets of PTL in LUAD were identified through network pharmacology, molecular simulation docking, and molecular dynamics simulations. Finally, the effects of PTL on amino acid metabolism and oxidative stress in LUAD were verified using in vivo and in vitro experiments.ResultsPTL treatment of LUAD cells resulted in significant changes in expression of 157 proteins. GO and KEGG enrichment analyses showed that these proteins were involved in amino acid metabolism and oxidative stress response. Targeted amino acid metabolomics further confirmed that PTL affected amino acid metabolism in LUAD. Network pharmacology, molecular docking, and molecular dynamics simulations identified GCTG as a potential target of PTL in LUAD. Meanwhile, in vitro and in vivo experimental results indicated that PTL targeting GCTG affected the proliferation, amino acid metabolism, and oxidative stress levels of LUAD cells.ConclusionPTL affects proliferation, amino acid metabolism, and oxidative stress levels of LUAD cells via targeting GCTG. Therefore, our study provides new insights into the prevention and treatment of LUAD with PTL, which may lay the foundation for future research directions